Nanoparticles Combining Gene Therapy and Chemotherapy as a Treatment for Gastrointestinal Tumors: A Systematic Review - Jorge Rodríguez-Criado; Francisco Quiñonero; Jose Prados; Consolacion Melguizo (Applied Sciences, 2024)
Gastrointestinal cancer is one of the greatest challenges for biomedical research, accounting for one-quarter of diagnoses and one-third of deaths nowadays, due to the existence of drug resistance mechanisms that prevent therapeutic efficacy in advanced stages. Nanotechnology has been shown to be an effective strategy for the evasion of this phenomenon, and gene silencing by siRNA makes it possible to decrease the expression of certain genes involved in chemoresistance and tumor progression. Our review analyzed studies published during the last 5 years that combined siRNA gene inhibition and chemotherapy as treatment of different gastrointestinal tumors. This review was carried out by searching PubMed, SCOPUS and WoS databases, where 49 articles were finally selected. The results showed that simultaneous encapsulation of siRNA targeting different genes involved in cancer and chemotherapy were more effective at the preclinical level compared to the administration of both treatments individually. The cytotoxic effect was generated through increased induction of apoptosis derived from the dysregulation of chemoresistance-related pathways, producing a decrease in tumor volume and an increase in survival of mice in in vivo assays. Therefore, the combination of both therapies in the same nanoformulation appears to be an interesting therapeutic strategy for the treatment of gastrointestinal tumors.